Capital structure in the Airline Industry – An Empirical study of determinants of capital structure - KHAZAALEH, FADI MOHAMMED KHALIL (2017)
In the business environment, decisions that are associated with the capital structure are very critical in nature. The strategic team of an organization is mainly involved in analyzing the appropriate capital structure for a company. The decisions of capital structure mainly involve decisions in respect of the portfolio mix of debt and equity. This research aimed to identify determinants of capital structure in the airline industry. Total of 8 airlines belonging to different countries were selected for this study. Data for a period of five years for the mentioned airlines were collected and panel regression was done. The airlines selected for the study were Southwest Airlines, British Airways, Emirates Airlines, Singapore Airlines, South African Airlines, Oman Air, Turkish Airlines and Air New Zealand. Out of the 13 determinants that were identified based on literature review, the results of the study showed that profit, size, leasing policies, ownership, and difference of return and average return (study period) are the determinants the capital structure in the airline industry